2013
DOI: 10.1007/s10517-013-1950-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Renin–Angiotensin System Genes in Brain Structures of ISIAH Rats with Stress-Induced Arterial Hypertension

Abstract: We studied the expression of genes encoding angiotensinogen (Agt), renin (Ren), angiotensin-converting enzyme (ACE), and type 1 angiotensin receptor (AT1A) in the hypothalamus and medulla oblongata of hypertensive ISIAH rats and normotensive WAG rats. The amount of Agt mRNA in the hypothalamus of young ISIAH rats was increased by 30% compared to WAG controls. In the medulla oblongata of young ISIAH rats, the levels of mRNA of Agt and AT1A receptor were enhanced by 60% and 24%, respectively, compared to WAG rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The results of several studies indicate the presence of increased basal activity in the cerebral RAAS of ISIAH rats [17,53]. This observation is confirmed by the finding that the blockade of the brain RAAS lowers BP in ISIAH rats [18].…”
Section: Characteristics Of the Main Neuroendocrine Pathwaysmentioning
confidence: 64%
See 1 more Smart Citation
“…The results of several studies indicate the presence of increased basal activity in the cerebral RAAS of ISIAH rats [17,53]. This observation is confirmed by the finding that the blockade of the brain RAAS lowers BP in ISIAH rats [18].…”
Section: Characteristics Of the Main Neuroendocrine Pathwaysmentioning
confidence: 64%
“…Immunoblotting analysis [16] Increased basal activity of the central (brain) renin-angiotensin-aldosterone system (RAAS) in ISIAH rats. The RAAS is inhibited in the kidneys of adult ISIAH rats Real-time PCR [17][18][19] Homozygosity of ISIAH rats DNA fingerprinting [20] Genetic specificity of the ISIAH rat strain Single nucleotide polymorphisms (SNPs) [21,22] Steps toward drug discovery and translational medicine A long-term reduction in basal and stress-induced BP has been obtained via injections of dopamine precursor L-DOPA during early development (21-25 days after birth).…”
Section: Phenotype Approach Referencesmentioning
confidence: 99%
“…Human ANG is a glycoprotein that is composed of 485 residue amino acids. The liver is considered the main source of ANG, but other organs and cells such as the heart, kidney, brain, and leukocytes can express ANG in pathophysiological conditions ( Gomez et al, 1993 ; Tamura et al, 1998 ; Kobori et al, 2007 ; Klimov et al, 2012 ). Subsequently, the angiotensin-converting enzyme (ACE), expressed in many tissues, cleaves the C-terminal dipeptide from Ang I to produce Angiotensin II (Ang II) octapeptide.…”
Section: The Renin-angiotensin System and Its Counter-regulatory Armmentioning
confidence: 99%
“…Changes in myocardium and vessels (typical for hypertension); violations in adrenergic system of the brain, kidneys, and heart (Amstislavsky, 1986;Klimov et al, 2013); functional and morphological changes in kidneys and adrenal glands (Buzueva et al, 2006;Amstislavsky et al, 2006;Pyl'nik et al, 2012); biochemical changes at the level of cellular mem branes (namely, in ion transporting systems of the cell) (Markel et al, 1992); and a number of other vio lations were found in ISIAH rats. In total, increased activity of the hypothalamic-pituitary-adrenal sys tem is typical for ISIAH (Markel et al, 2007;Antonov et al, 2010;Klimov et al, 2013).…”
Section: Genetic Models Of Arterial Hypertensionmentioning
confidence: 99%